Cannabinoid type 1 receptor ligands WIN 55,212-2 and AM 251 alter anxiety-like behaviors of marmoset monkeys in an open-field test - Cagni, Priscila; Barros, Marilia (Behavioural brain research, 2013)
► Single brief exposure to open-field induced anxiety-related behaviors in marmosets. ► Cannabinoid type 1 receptor ligands attenuated anxiety-related behaviors in marmosets. ► Endocannabinoid system exerts complex role on anxiety in nonhuman primates. Cannabinoid type 1 receptors (CB1r) are an important modulatory site for emotional behavior. However, little is known on the effects of CB1r ligands on emotionality aspects of primates, even with their highly similar behavioral response and receptor density/distribution as humans. Thus, we analyzed the effects of the CB1r agonist WIN 55,212-2 (WIN; 1mg/kg) and the antagonist AM 251 (AM; 2mg/kg), systemically administered prior to a single brief (15min) exposure to a novel open-field (OF) environment, on the behavior of individually tested adult black tufted-ear marmosets. Both WIN- and AM-treated subjects, compared to vehicle controls, had significantly lower rates of long (contact) calls and exploration, while higher levels of vigilance-related behaviors (scan/glance); these are indicators of anxiolysis in this setup. Changes in locomotion were not detected. However, in the vehicle and AM-groups, sojourn in the peripheral zone of the OF was significantly higher than in its central region. WIN-treated marmosets spent an equivalent amount of time in both zones. Therefore, activation or blockade CB1r function prior to a short and individual exposure to an unfamiliar environment exerted a significant and complex influence on different behavioral indicators of anxiety in these monkeys (i.e., a partially overlapping anxiolytic-like profile). AM 251, however, has no anxiolytic effect when the time spent in the center of the OF is considered. This is a major difference when compared to the WIN-treated group. Data were compared to the response profile reported in other pre-clinical (rodent) and clinical studies.